Case report: Endoscopic frontal sinus opening surgery for noninflammatory frontal sinus headache: A short case series - Xie, Yan; Wu, Shiqi; Cui, Wanling; Zeng, Dandi; Chen, Feifei; Liang, Fangqi; Lu, Rongrong; Zhang, Chenyu; Jiang, Luyun (Frontiers in Surgery, 2023)
Objective The objectives of this study were to analyze rhinogenic headache, i.e., noninflammatory frontal sinus headache, a headache caused by bony obstruction of the frontal sinus drainage channels that receives relatively insufficient attention clinically, and to propose endoscopic frontal sinus opening surgery as a treatment based on the etiology. Study Design Case series. Setting From the data of patients with noninflammatory frontal sinus headache who underwent endoscopic frontal sinus surgery in Hospital of Chengdu University of Traditional Chinese Medicine during 2016–2021, data for three cases with detailed postoperative follow-up data were extracted for case series reports. Methods This report provides detailed information on three patients with noninflammatory frontal sinusitis headache. Treatment options include surgery and rechecking, with the visual analogue scale (VAS) scores of preoperative and postoperative symptoms, CT, and endoscopic images. Three patients had common characteristics: the clinical manifestations were recurrent or persistent with pain and discomfort in the forehead area, but there was no nasal obstruction or runny nose; the paranasal sinus CT revealed no signs of inflammation in the sinuses but suggested bony obstruction of the drainage channel of the frontal sinus. Results All three patients had recovery from headache, nasal mucosal recovery, and patent frontal sinus drainage. The recurrence rate of forehead tightness and discomfort or pain was 0. Conclusion Noninflammatory frontal sinus headache does exist. Endoscopic frontal sinus opening surgery is a feasible treatment modality that can largely or even completely eliminate the stuffy swelling and pain in the forehead. The diagnosis and surgical indications for this disease are based on a combination of anatomical abnormalities and clinical symptoms.